The Effects of Motor and Vocal Response Interruption and Redirection on Vocal Stereotypy and Appropriate Vocalizations. (April 2015) - Shawler, Lesley A.; Miguel, Caio F.
<x xml:space="preserve">Abstract</x> Stereotypy has been defined as repetitive vocal or motor behaviors that are noncontextual with invariant topographies. One intervention to reduce vocal stereotypy and increase appropriate vocalizations is response interruption and redirection (RIRD). Previous research has suggested that RIRD's behavioral mechanism consists of punishment. The purpose of this study was to extend this research by comparing two procedures, namely, vocal and motor RIRD contingent upon the occurrence of vocal stereotypy and to evaluate concomitant increases in appropriate vocalizations. A multiple treatment reversal design was used to compare the effectiveness of both interventions on five children diagnosed with an Autism Spectrum Disorder. Results suggested that both demand topographies were equally effective in reducing vocal stereotypy and increasing appropriate vocalizations. This research replicates previous findings that have suggested that RIRD is a punishment procedure. Copyright © 2015 John Wiley & Sons, Ltd.